Analisis Momen-Rotasi Sambungan Haunched Gusset Plate Balok Kolom Baja Canai Dingin Menggunakan Metode Elemen Hingga - Irwandra Septiadi; Kiagus Muhammad Aminuddin; Muhammad Firdaus; Bazar Asmawi; Verinazul Septriansyah; Adji Sutama (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2026)
The increasing use of cold-formed steel (CFS) in building structural systems requires an accurate understanding of connection behavior, particularly beam–column connections which have an important role in transferring moment and rotation. One connection type that has been developed is the haunched gusset plate (HGP), which is designed to improve stress distribution and rotational performance of the joint. This study aims to analyze the moment–rotation characteristics of HGP connections in CFS beam–column structures with double channel sections using a numerical approach based on the Finite Element Method (FEM) implemented in ANSYS Workbench. The numerical model was developed based on the IJT-BGJ-9 experimental specimen from previous studies as a validation reference, considering material nonlinearity, boundary conditions, contact interaction, and explicit bolt modeling. The analysis focuses on the evaluation of joint strength capacity, stiffness capacity, and ductility capacity in accordance with the provisions of BS EN 1993-1-8. The results show that the FEM moment–rotation curve has very good agreement with the experimental results, with a rotation difference of 0,43% and a final stiffness difference of 1,30%. The HGP connection is classified as a semi-rigid, partial-strength, and ductile joint. These findings demonstrate that the developed FEM model is able to accurately represent the actual behavior of the connection and can be used as a reliable and efficient evaluation tool for the analysis and design of cold-formed steel frame connections.